Exploring the Impact of Socioeconomic Factors on Stress Levels Using Clustering in Southeast Asia during the COVID-19 Pandemic - Rahmat, Shafa Khadijah; Sabila, Fatsa Vidyaningtyas (Indonesian Journal of Applied Mathematics and Statistics, 2024)
This paper explores the impact of socioeconomic factors on stress levels across Southeast Asia during the COVID-19 pandemic. Data from the COVIDiSTRESS Global Survey were analyzed using regression analysis to identify key determinants along with clustering techniques, such as DBSCAN to group similar behavioral responses. Variables such as income, employment status, education level, and healthcare access were considered. The findings reveal significant disparities in stress levels related to socioeconomic conditions. For instance, countries with lower socioeconomic indicators, such as Vietnam and the Philippines, show high perceived stress levels (58,9% and 76,2% respectively). Conversely, countries with higher socioeconomic stability, like Brunei, exhibit moderate stress levels at 60%. These results underscore the importance of addressing socioeconomic inequalities to mitigate stress and enhance mental resilience across Southeast Asia.